2020
DOI: 10.1038/s41598-020-72067-7
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis exosomes stimulate monocytes to produce pro-inflammatory cytokines and CCL2

Abstract: Pulmonary sarcoidosis has unknown etiology, a difficult diagnostic procedure and no curative treatment. Extracellular vesicles including exosomes are nano-sized entities released from all cell types. Previous studies of exosomes from bronchoalveolar lavage fluid (BALF) of sarcoidosis patients have revealed pro-inflammatory components and abilities, but cell sources and mechanisms have not been identified. In the current study, we found that BALF exosomes from sarcoidosis patients, but not from healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A previous study has shown that exosomes contribute to the pathogenesis of asthma (11). Additionally, exosomes from the broncho alveolar lavage fluid (BALF) of sarcoidosis patients can induce the expression of CCL2 (MCP1) (41). Here, we showed that exosomes from antigen-stimulated RBL2H3 cells increased the expression of MCP1 in B16F1 melanoma cells (Figure 7C) and lung macrophages (Figure 7E).…”
Section: Discussionsupporting
confidence: 57%
“…A previous study has shown that exosomes contribute to the pathogenesis of asthma (11). Additionally, exosomes from the broncho alveolar lavage fluid (BALF) of sarcoidosis patients can induce the expression of CCL2 (MCP1) (41). Here, we showed that exosomes from antigen-stimulated RBL2H3 cells increased the expression of MCP1 in B16F1 melanoma cells (Figure 7C) and lung macrophages (Figure 7E).…”
Section: Discussionsupporting
confidence: 57%
“…For some patients, the potent chemotactic agent, C–C motif chemokine ligand 2 (CCL2) was also increased in PBMCs by exosomes. Interestingly, the exosome-driven increase of CCL2 was subsequently reduced by addition of a cysteinyl leukotriene receptor antagonist—montelukast [ 33 ], used as an asthma drug [ 34 ]. The abovementioned research showed possible roles of exosomes as mediators in inflammation progression and a potential target in sarcoidosis treatment.…”
Section: Balf-evs Modulate Inflammation In Pulmonary Diseasesmentioning
confidence: 99%
“…In the same manner, focus could be placed on EXOSC2 (Exosome Component 2) targeted by the SARS-CoV2 protein NSP8, also known as ribosomal RNA-processing protein-4 (RRP4), an essential component of exosomes or extracellular vesicles acting as intercellular transmitters, and a scavenger of microbial RNA and infectious agents [95]. Broncho-alveolar lavage fluid of sarcoidosis patients showed increased levels of exosomes inducing various pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF (Tumor Necrosis Factor) alpha [96]. One may expect that any deficiency in autophagy-either autophagosome maturation or autolysosome formation-may induce a shift towards the endosomal-exosome pathway through the fusion of autophagosomes to multivesicular bodies (MVB) and the release in exosomes [97,98].…”
Section: Endoplasmic Reticulum Stress-related Pathwaysmentioning
confidence: 99%